2015
DOI: 10.1038/mi.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

In situ hematopoiesis: a regulator of TH2 cytokine-mediated immunity and inflammation at mucosal surfaces

Abstract: Hematopoiesis refers to the development of blood cells in the body through the differentiation of pluripotent stem cells. Although hematopoiesis is a multifocal process during embryonic development, under homeostatic conditions it occurs exclusively within the bone marrow. There, a limited number of hematopoietic stem cells differentiate into a rapidly proliferating population of lineage-restricted progenitors that serve to replenish circulating blood cells. However, emerging reports now suggest that under inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 126 publications
0
25
0
Order By: Relevance
“…46,47 It has been shown that numbers of IL-5-responsive EoPs are higher in the blood of patients with allergic asthma compared with healthy control subjects 44 and that these cells are increased within the airways after allergen or IL-5 challenge in patients with atopic asthma, where the increase in EoP precedes the development of airway eosinophilia. 42,48,49 Consistent with these findings, the current study demonstrated that EoP numbers are increased in the blood and airways of patients with severe compared with mild asthma.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 It has been shown that numbers of IL-5-responsive EoPs are higher in the blood of patients with allergic asthma compared with healthy control subjects 44 and that these cells are increased within the airways after allergen or IL-5 challenge in patients with atopic asthma, where the increase in EoP precedes the development of airway eosinophilia. 42,48,49 Consistent with these findings, the current study demonstrated that EoP numbers are increased in the blood and airways of patients with severe compared with mild asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, hematopoietic progenitor cells are progeny of hematopoietic stem cells, but unlike stem cells, have limited self-renewal capacity and restricted lineage potential. CD34, a surface marker often used to identify hematopoietic stem/progenitor cells (HSPCs), is downregulated as HSPCs mature with the exception of some mast cells (5). HSPCs are mainly present in a specialized bone marrow niche that regulates their survival, proliferation, self-renewal and differentiation (5).…”
Section: Innate Immunitymentioning
confidence: 99%
“…CD34, a surface marker often used to identify hematopoietic stem/progenitor cells (HSPCs), is downregulated as HSPCs mature with the exception of some mast cells (5). HSPCs are mainly present in a specialized bone marrow niche that regulates their survival, proliferation, self-renewal and differentiation (5). Hematopoiesis typically occurs in the bone marrow in response to signals received from stromal cells and growth factors.…”
Section: Innate Immunitymentioning
confidence: 99%
See 2 more Smart Citations